Model penilaian Kirkpatrick: mengkaji pengaruh komunikasi terhadap keberkesanan latihan - Abdul Manan, Kamaruzzaman; Md Noor, Shuhaida; Omar, Bahiyah (Penerbit UKM, 2013)
This research aims to measure the impact of communication on training effectiveness using the Kirkpatrick Evaluation Model which features four levels of evaluation: Level I - reaction; Level II - learning; Level III - behaviour, and Level IV - results. Trainee reactions towards communication dimensions, measured at Level I, is critical to trainee evaluation because it is regarded as the precondition to the next three levels of evaluation. In enhancing the Kirkpatrick Evaluation Model, the researchers also investigate factors that influence trainees’ learning and their confidence in applying what they have learnt at the work place. Additionally, to address the concerns raised in previous studies about the difficulties in measuring Level IV – results, this study introduces an evaluation method that combines trainees’ and supervisors’ evaluation that results ina more comprehensive evaluation. The data for this study was collected through the distribution ofquestionnaires to 200 respondents at Universiti Sains Malaysia (USM). This research provides evidence that there is a strong relationship between communication and trainees’ learning. This research also found that trainees’ confidence in applying their knowledge from training is an important factor in providing an accurate prediction of trainees’s behaviour change (i.e. application of knowledge in a work environment) more accurately.